Overexpression of Wnt5a Promotes Angiogenesis in NSCLC. (5th June 2014) - Yao, Lingli; Sun, Baocun; Zhao, Xiulan; Zhao, Xueming; Gu, Qiang; Dong, Xueyi; Zheng, Yanjun; Sun, Junying; Cheng, Runfen; Qi, Hong; An, Jindan
Abstract : To evaluate Wnt5a expression and its role in angiogenesis of non-small-cell lung cancer (NSCLC), immunohistochemistry and CD31/PAS double staining were performed to examine the Wnt5a expression and we analyze the relationships between Wnt5a and microvessel density (MVD), vasculogenic mimicry (VM), and some related proteins. About 61.95% of cases of 205 NSCLC specimens exhibited high expression of Wnt5a. Wnt5a expression level was upregulated in the majority of NSCLC tissues, especially in squamous cell carcinoma, while its expression level in adenocarcinoma was the lowest. Wnt5a was also found more frequently expressed in male patients than in female patients. Except for histological classification and gender, little association was found between Wnt5a and clinicopathological features. Moreover, Wnt5a was significantly correlated with prognosis. Overall, Wnt5a-positive expression in patients with NSCLC indicated shorter survival time. As for vascularization in NSCLC, Wnt5a showed close association with VM and MVD. In addition, Wnt5a was positively related with β -catenin-nu, VE-cadherin, MMP2, and MMP9. The results demonstrated that overexpression of Wnt5a may play an important role in NSCLC angiogenesis and it may function via canonical Wnt signal pathway. This study will provide evidence for further research on NSCLC and also will provide new possible target for NSCLC diagnosis and therapeutic strategies.